Comparación de la respuesta de los sensores imu pololu-2763 Y MPU-6050 (2022)
The inertial measurement unit (IMU) is a device comprising an accelerometer that measures the change of force produced by the movement of the same, a gyroscope that records the change of position of the axes and a magnetometer that interacts with the earth's magnetic field. The present work exposes the comparison between two IMU sensors, for the measurement and implementation in the rotary wing propeller-beam (SHAR) project, previously developed in the SITAD (seedbed of research in analog and digital technologies), which consists of a platform for the study of control theory, where the selection of one of the IMU'S that has the characteristics required for its application is proposed. A series of steps must be followed for the study and analysis of the IMU'S comprised; selection of the method for the calculation of errors, acquisition of the electronic components, implementation of the test system, acquisition of data from the sensors and data analysis. The realization of these allows to consolidate the comparison of the IMU's with the objective of achieving the selection of one of these for the SHAR project and analysis for future applications.The inertial measurement unit (IMU) is a device comprised by; an accelerometer that measures the change of force produced by the movement of the same, a gyroscope that registers the change of position of the axes and a magnetometer that interacts with the earth's magnetic field.